Neoantigen-Specific Adoptive Cell Therapies for Cancer: Making T-Cell Products More Personal - Bianchi, Valentina; Harari, Alexandre; Coukos, George (Frontiers in Immunology, 2020)
Mutation-derived neoantigens are taking central stage as determinant in eliciting effective anti-tumor immune responses following adoptive T-cell therapies. These mutations are patient-specific and their targeting calls for highly personalized pipelines. The promising clinical outcomes of TIL therapy have spurred interest in generating T-cell infusion products that have been selectively enriched in neoantigen (or autologous tumor) reactivity. The implementation of an isolation step, prior to T-cell in vitro expansion and reinfusion, may provide a way to improve the overall response rates achieved to date by adoptive T-cell therapies in metastatic cancer patients. Here we provide an overview of the main technologies (i.e. pMHC multimers, cytokine capture and activation markers) to enrich infiltrating or circulating T-cells in predefined neoantigen specificities (or tumor-reactivity). The unique technical and regulatory challenges faced by such highly-specialized and patient-specific manufacturing T-cell platforms are also discussed.